Peran Posyandu Lansia Terhadap Kesehatan dan Kesejahteraan Lansia: Literature Review - Asma Ul-Husnah; Bachtiar Safrudin (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The increasing number of older adults has created various challenges in the health sector, particularly related to health maintenance, quality of life, and well-being. One community-based health service developed to support older adults is the Elderly Integrated Health Service Post. This study aimed to identify the role of Elderly Integrated Health Service Posts in supporting the health, quality of life, and well-being of older adults based on published research findings. This study employed a narrative literature review approach. Articles were selected purposively according to the research topic and predefined inclusion criteria. A total of 10 articles published between 2022 and 2025 were included in the review. Data were collected through reading, reviewing, and extracting important information from each article into a summary table and were analyzed narratively by comparing and grouping findings with similar themes. The review showed that Elderly Integrated Health Service Posts contribute to improving health, quality of life, and well-being through health examinations, health monitoring, health education, physical activities, and social activities. These services also support social interaction, independence, and access to health care among older adults. However, their utilization is still influenced by participation levels, family support, accessibility of services, and program implementation. Elderly Integrated Health Service Posts can serve as an important community-based strategy to support healthy, active, and independent ageing. Strengthening the roles of families, community health volunteers, and health professionals is necessary to optimize service utilization.